Teorias semiclássica e efetiva da gravitação - Paszko, R [UNESP] (2006)
First and second order corrections for the scattering of diﬀerent types of particles by a weak gravitational ﬁeld, treated as an external ﬁeld, are calculated. These computations indicate a violation of the Equivalence Principle: to ﬁrst order, the cross-sections are spin dependent; if the calculations are pushed to the next order, they become dependent upon energy as well. Interesting enough, the aforementioned results are equivalent to those obtained by means of the so-called Eﬀective Theory of Gravitation, in the limit in which one of the masses is much greater than all the other energies involved. We discuss also some applications of our research, such as the determination of an upper bound for the photon mass, and the possible detection, in the foreseeable future, of these violations of the Equivalence Principle